Deprivasi Utama Kemiskinan Multidimensi Antarprovinsi di Indonesia - Sumargo, Bagus; Simanjuntak, Naomi Miduk M. (Jurnal Ekonomi dan Pembangunan Indonesia, 2019)
So far poverty alleviation policies are still oriented to the monetary approach, while poverty is multidimensional, this means that multidimensional poverty is defined as the condition of the lack of all existing poverty indicators. This study finds the main deprivation of poverty indicators in each province in Indonesia, so that poverty alleviation programs can be directed and more in line with the main deprivation needs of poverty in an area. Using the data of the National Socio-Economic Survey (Susenas 2014) and Alkire-Foster’s multidimensional poverty measurement method, and with 12 indicators in three dimensions (health, education, and living standards), found that a priority scale of poverty alleviation assistance required by all provinces in Indonesia based on deprivation primarily a relief program that deals with old school problems and immunizations, except in Maluku province is a birth attendant and in Papua is a literacy issue.